2019
DOI: 10.1155/2019/2424518
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Flexural Behavior of Prestressed Concrete Beams Reinforced by CFRP under Chloride Environment

Abstract: In order to study the effects of initial damages, CFRP reinforcement, and chloride corrosion on the flexural behavior of prestressed concrete beams, ten prestressed concrete beams were designed and manufactured, which were preloaded with 0%, 40%, and 60% of the ultimate load to crack. Then, part of the beams were reinforced by CFRP and immersed in chloride condition for 120 days. After that, the four-point bending tests were performed. Then, the sectional strain, deformation, flexural stiffness, flexural capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The studies are grouped in order to clearly distinguish the members subjected to different corrosion processes (natural or accelerated). Among them, four articles [29][30][31][32] dealt with the behavior of beams extracted by a decommissioned bridge (DB_N); three works [33][34][35] investigated the performance of beams with reduced dimensions with respect to the previous ones and subjected to a naturally corrosive environment (B_N); eleven papers [36][37][38][39][40][41][42][43][44][45][46][47] experimentally tested the flexural performance of PRC beams damaged by artificial corrosion (B_A). • ∆R max *** ∼ = 50% for the beam with some wire cross-section loss up to 75%.…”
Section: Review Of Performed Experimental Tests On Corroded Prc Beamsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies are grouped in order to clearly distinguish the members subjected to different corrosion processes (natural or accelerated). Among them, four articles [29][30][31][32] dealt with the behavior of beams extracted by a decommissioned bridge (DB_N); three works [33][34][35] investigated the performance of beams with reduced dimensions with respect to the previous ones and subjected to a naturally corrosive environment (B_N); eleven papers [36][37][38][39][40][41][42][43][44][45][46][47] experimentally tested the flexural performance of PRC beams damaged by artificial corrosion (B_A). • ∆R max *** ∼ = 50% for the beam with some wire cross-section loss up to 75%.…”
Section: Review Of Performed Experimental Tests On Corroded Prc Beamsmentioning
confidence: 99%
“…Liu et al [45] conducted experimental testing on five PRC beams using four-point bending. A very low initial prestressing action of 558 MPa, only 0.30 times the nominal strand yield strength, was applied.…”
Section: Artificially Corroded Prc Beamsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the research and application of retrofitting and rehabilitating concrete structures with carbon fiber-reinforced polymer (CFRP) has developed incrementally and rapidly [2,3]. A number of studies have shown that the application of CFRP as an external strengthening system would effectively increase the ultimate loading carrying capacity and flexural stiffness of corroded RC beams [4][5][6][7][8][9], but the shortcoming lies in the significant reduction in the deflection capacity of beams and their ductility [10]. Meanwhile, some problems have emerged with the usage of externally bonded CFRP composites, including high cost, poor high-temperature resistance, no waterproofing of surfaces, incompatibility of epoxy resins and cement-substrate materials, and environmental hazards [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%